High Temperature Polymer Electrolyte Membrane Fuel Cells Approaches, Status, and Perspectives - Li, Qingfeng; Aili, David; Hjuler, Hans Aage; Jensen, Jens Oluf (Springer International Publishing : Imprint: Springer, 2016)
This book is a comprehensive review of high-temperature polymer electrolyte membrane fuel cells (PEMFCs).  PEMFCs are the preferred fuel cells for a variety of applications such as automobiles, cogeneration of heat and power units, emergency power, and portable electronics. The first 5 chapters of the book describe rationalization and illustration of approaches to high temperature PEM systems. Chapters 6 - 13 are devoted to fabrication, optimization and characterization of phosphoric acid-doped polybenzimidazole membranes, the very first electrolyte system that has demonstrated the concept of and motivated extensive research activity in the field. The last 11 chapters summarize the state-of-the-art of technological development of high temperature-PEMFCs based on acid doped PBI membranes including catalysts, electrodes, MEAs, bipolar plates, modelling, stacking, diagnostics and applications.